2021
DOI: 10.11606/s1518-8787.2021055002134
|View full text |Cite
|
Sign up to set email alerts
|

Padrões de amamentação e fatores associados ao desmame precoce na Amazônia ocidental

Abstract: OBJETIVO: Caracterizar os padrões de amamentação nos primeiros seis meses de vida e fatores associados ao desmame precoce numa coorte de nascidos vivos em Rio Branco, Acre. MÉTODOS: Estudo prospectivo com nascidos vivos entre abril e junho de 2015. As entrevistas com as mães ocorreram logo após o nascimento e entre 6 e 15 meses pós-parto. Na alta hospitalar, o aleitamento foi definido em exclusivo (AME) e materno (AM). No seguimento, os padrões de amamentação foram AME, aleitamento materno predominante (AMP) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
2
6
0
6
Order By: Relevance
“…Our estimate was lower than the prevalence of prelacteal feeding found in LMICs (33.9%) from 2010 to 2019 18 and the prevalence of formula supplementation during hospital stay reported by a Canadian population-based birth cohort study (25.9%) conducted between 2009 and 2012 19 . However, it was similar to that found in a cohort study conducted in Rio Branco, Acre state, where 15% of the infants received formula supplementation before hospital discharge 10 . A recent retrospective cohort study including 85 LMICs has shown that prelacteal feeding was inversely associated with EBF in children under six months of age.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our estimate was lower than the prevalence of prelacteal feeding found in LMICs (33.9%) from 2010 to 2019 18 and the prevalence of formula supplementation during hospital stay reported by a Canadian population-based birth cohort study (25.9%) conducted between 2009 and 2012 19 . However, it was similar to that found in a cohort study conducted in Rio Branco, Acre state, where 15% of the infants received formula supplementation before hospital discharge 10 . A recent retrospective cohort study including 85 LMICs has shown that prelacteal feeding was inversely associated with EBF in children under six months of age.…”
Section: Discussionsupporting
confidence: 87%
“…Given the current challenging scenario, local investigations on breastfeeding duration predictors, together with general data provided by nationwide surveys, are crucial to optimize public health efforts, especially among vulnerable populations. However, few studies have focused on factors affecting BF rates among Amazonian children 8 10 , who have the most unfavorable living conditions in Brazil 11 . We hypothesized that sociodemographic, obstetric, perinatal, and mother-child characteristics at early life would be associated with EBF and BF duration in an urban Amazonian setting.…”
Section: Introductionmentioning
confidence: 99%
“…Os esforços de saúde pública devem priorizar o AME, promover o aleitamento materno na primeira hora de vida e prevenir o consumo de álcool durante a gravidez, amamentação cruzada e o uso de chupeta. (Martins et al, 2021).…”
Section: Discussionunclassified
“…Com o objetivo de caracterizar os padrões de aleitamento materno nos primeiros seis meses de vida e fatores associados ao desmame precoce, foi realizada uma coorte de nascimento em Rio Branco, Acre, Brasil, através de um estudo prospectivo entrevistando mães logo após o nascimento de seus bebês e entre 6 e 15 meses pós-parto. Em conclusão, dentre as crianças que receberam alta hospitalar em AM, o risco de desmame precoce foi maior para aqueles bebês que: usaram chupeta, não foram amamentadas na primeira hora de vida e mães que consumiram álcool durante a gravidez (Martins et al, 2021).…”
Section: Uso Da Chupeta E O Aleitamento Maternounclassified
“…(26) Confirmando esses achados, estudo de coorte conduzido na capital do Acre identificou que a ausência de aleitamento materno na primeira hora de vida foi associada ao desmame precoce. (27) Um dos aspectos para que essa prática seja pouco executada é a rotina imposta pelos profissionais de saúde dentro da sala de parto em relação aos primeiros cuidados com o recém-nascido, retardando o contato mãe e filho e a amamentação na primeira hora de vida.…”
Section: Discussionunclassified